Analisis Dampak Kegiatan Wisata Terhadap Kualitas Air Sungai Betimus Kecamatan Sibolangit Kabupaten Deli Serdang - Ghanang Dhika Aria; Pindi Patana; Rusdi Leidonald (AQUACOASTMARINE, 2014)
River is one of the most important sources of water for human, because it can serve as a source of drinking water, tourism, animal husbandry, and fishery. Positive impact of tourism activities in economic development can also lead to negative effects of environmental degradation. Therefore, a research had been conducted at Betimus River District of Sibolangit, Region of Deli Serdang in June– July 2013 by analyzing the water quality of Betimus Riverand compare it with the water quality standards based on PP No 82 tahun 2001and perceptions of visitors and managers. The Waters quality parameters thatanalyzed, i.e, stream. temperature, brightness, dissolved oxygen,pH, BOD5, ammonis,Colifaecal, and perceptions of visitors. The results showed that water quality value for eight parameters of Betimus River was meet the standard of quality based on PP No 82 tahun 2001 and visitors felt comfortable with these attractions.Key Words :Colifaecal, Betimus River, Tourism, Water Quality.